The Influences of the Anthropogenic Agents in Increasing the Temperature for Various Emission Scenarios. - Najaf, Ahmed; Al-Khafagi, Amer; Jamil, Dalia (Iraqi Journal of Science, 2024)
Predicting future climate regionally and by space images and landscape studies indicate that the major influences is the increasing of carbon dioxide which attain to more than 350 ppm. The evidences accordingly refer to the increase in the earth temperature which attains to approximately 4 C◦ and 7.2 F◦ causes rapid inversion and changing the climate, so the surface air temperature is 22 C◦ in 1999 will be accordingly more than 26 C◦ in 2090.